AI Interview Trainer - Sopan Bhere; Dudhat, Sejal (MultiTech Publisher, 2023)
Nowadays AI is playing a crucial role in our daily life such as in the medical field, IT industry, Education, and so on. In this paper, we introduced a new AI bot that helps you to get a job in various fields like the IT industry, Education, etc. Next, we discuss the technology used for developing AI Bot such as Artificial Intelligence, Machine Learning, and Deep Learning as well as various frameworks that help to develop Bot such as Natural Language Processing (NLP), Translator (speechto-text and text-to-speech), Speech analysis, etc. The aim of developing this project is to user can identify their strength, weaknesses, and personality improvement to succeed in an interview. AI bots can be considered as a substitution for human beings in terms of interaction.